Mad Hatter with Inverted follicular keratosis on elective site - Mazzotta, F. (European Journal of Pediatric Dermatology, 2015)
The infectious complications of tattoos significantly decreased due to better sanitation; however, allergic reactions and tumors occurring on tattoos are yet described in the literature. The short space of time between execution of the tattoo and appearance of the tumor and the onset of a tumor and related metastases on only one chromatic component of the tattoo, usually red, would induce to think of a cause-effect relationship between tattoo and cancer (1); however, the discrepancy between the number of tattooed people who arrive in the US to 25% of the population between 18 and 50 (2) and number of tumors - less than 100 so far - is such as to conclude for a mere coincidence (1). The peculiarity of our case consists in the fact that it is the first reporting of an inverted follicular keratosis on tattoo; curious is its location within the tattoo in a venue - the face – in which most often is localized the tumor in reality.